Time-varying Risks of Construction Projects. (2015) - Toth, Tamas; Sebestyen, Zoltan
Abstract: Although risk management has become an integral part of project management generally insomuch that its application is required even by standards, it is usually left to project managers to define the required processes in detail and only little relevant methodological literature is available to provide further theoretical content. Known practices can still be developed in many parts, since in current approaches it is especially difficult to reflect on e.g. a phenomenon that individual risks typically decline and then disappear as construction progresses. This article focuses on declining and disappearing risk changing with time, based on value-based risk monitoring. For providing the mathematical background of time-varying risks, it is important to detect and monitor risks related to the added value of the project. Consequently, if necessary, it is possible to start action plans to avoid losses. In a construction project, in order to maintain a value-based risk management process, a continuous valuation method is necessary which is able to capture the value of the building in its current state. Our aim is twofold: to develop an evaluation method, which is able to determine the current market value of a project in the construction phase, and to provide a risk monitoring tool, which reflects the phenomenon of time-varying risks.